Heterogeneous integration approach based on flip-chip bonding and misalignment self-correction elements for electronics-optics integration applications - Tung, Bui Thanh; Suzuki, Motohiro; Kato, Fumiki; Nemoto, Shunsuke; Aoyagi, Masahiro (Vietnam Journal of Mechanics, 2012)
This paper presents a high precision bonding approach, capable of submicron alignment accuracy, based on the thermosonic flip-chip bonding technique and misalignment self-correction elements. The precision of the bonding technique is guaranteed by using of misalignment self-correction bump (convex) and hollow (concave) elements. Metal cone bump and conductive sloped hollow bonding pad elements are created using micro-machining techniques, on a chip specimen and substrate, respectively. The chip and substrate are bonded face-to-face using of an ultrasonic-enhanced flip-chip bonder. By introducing of misalignment self-correction elements, repeatable bonding accuracies of less than 500 nm were confirmed through experimental investigation. Bond properties, including electrical and mechanical properties, are also characterized to confirm the success of the bonding approach. With the obtained results, the proposed bonding approach is capable of being use in electronics-optics heterogeneous integration applications.